Collaboration in Designing a Pedagogical Approach in Information Literacy - Landøy, Ane; Popa, Daniela; Repanovici, Angela (Springer Texts in Education,, 2020)
This Open Access book combines expertise in information literacy with expertise in education and teaching to share tips and tricks for the development of good information literacy teaching and training in universities and libraries. It draws on research, knowledge and pedagogical practice from academia, to teach students how to sift through information to be able to distinguish the important and correct from the unusable. It discusses basic concepts and models of information literacy, as well as strategies for accessing, locating and retrieving information and methods suitable for the assessment and management of information. The book explains many concepts connected to information literacy and discusses pedagogical issues with a view to supporting the practitioner. Each chapter examines one aspect of information literacy, discusses the pedagogical challenges involved and provides suggestions for best practice.